The Consequences of Divorce Law on Common Property under Marriage Law & KHI - Aldya Khaira Almeyda; Ahmad Khisni (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The distribution of joint assets according to the provisions of Article 37 of Act No. 1 of 1974 concerning Marriage is not clearly stipulated how much each husband or wife is divorced, either divorced or divorced. Article 37 paragraph (1) states that if a marriage breaks up due to divorce, the joint property is regulated according to their respective laws. In the explanation of Article 37 paragraph (1), it is emphasized that the respective laws are religious law, customary law and other laws related to the distribution of the joint property. In addition to Act No. 1 of 1974 concerning Marriage, the Compilation of Islamic Law also applies in Indonesia, which relates to the distribution of joint assets as regulated in Articles 96 and 97 of the Compilation of Islamic Law. Based on these things, the problems that will be examined in this research are: what are the legal consequences of settling disputes on joint property according to Marriage Act No. 1 of 1974 and KHI, and what are the views of Islamic law regarding the distribution of joint assets after divorce, as well as the obstacles to the implementation of the distribution of joint assets in practice at the Salatiga Religious Court, Central Java Province.